Differential effects of fine and coarse particulate matter on hospitalizations for ischemic heart disease: A population-based time-series analysis in Southwestern China. (1st March 2020) - Liu, Si; Wang, Liya; Zhou, Li; Li, Weihao; Pu, Xiaorong; Jiang, Jingwen; Chen, Yucheng; Zhang, Li; Qiu, Hang
Abstract: Few studies have explored the associations of ischemic heart disease (IHD) hospitalizations with fine (diameter ≤ 2.5 μm, PM2.5 ) and coarse particulate matter (diameter between 2.5 and 10 μm, PMC ) simultaneously; and studies to distinguish the susceptible populations by sex, age, and comorbidity status are sparse and inconsistent. This study aimed to assess the differential effects of PM2.5 and PMC on IHD hospitalizations and to investigate modifiers of demographic characters, causes of hospitalizations, and comorbidity status on these differential effects. A time-series analysis using an over-dispersed generalized additive model on 33017 IHD hospitalizations was conducted in urban areas of Chengdu, Southwestern China, from 1 January 2015 to 31 December 2016. Z-test was used to test whether PMC - or PM2.5 -related effects were differential within each modifier. Furthermore, to evaluate the robustness of the key findings for gaseous pollutants exposure adjustment, co-pollutant models were constructed. We identified differential effects of PM2.5 and PMC on IHD hospitalizations in terms of the effect magnitude, effect stability, and susceptible populations. A 10 μg/m³ increment of PM2.5 and PMC at lag06 was associated with a 1.2% (95% confidence interval (CI): 0.3%, 2.2%) and 2.5% (95%CI: 1.1%, 3.8%) increase in IHD hospitalizations, respectively. After adjustment for gaseous pollutants, PMC effect was independent, particularly among males, angina, chronic IHD, and patients with comorbidity of chronic heart failure, hypertension, or chronic obstructive pulmonary disease (COPD); whereas, PM2.5 effect remained significant among patients with comorbidity of hypertension. Males, comorbidity of hypertension or COPD substantially increased the PMC -related risk for IHD hospitalizations; whereas, only comorbidity of hypertension increased the PM2.5 -related risk for IHD hospitalizations. Interestingly, the PMC effect was comparable between the middle-aged and the elderly. Our study found differential effects of PM2.5 and PMC on IHD hospitalizations and identified susceptible populations, which are important to establish guidelines or recommendations for high-risk individuals. Graphical abstract: Image 1 Highlights: Differential effects of PM2.5 and PMC on IHD hospitalizations were observed. Effect of PMC on IHD hospitalizations was about double that of PM2.5 . Comorbidity of hypertension enhanced PM2.5 -related risk for IHD hospitalizations. Males, comorbidity of hypertension or COPD increased the PMC -related risk. The PMC effect was comparable between the middle-aged and the elderly.